Pencegahan Tuberkulosis dalam Keluarga Melalui Media Rekaman Video - Sartika Sartika; Sigit Mulyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of providing education using video recording media in preventing tuberculosis in the family. The method used is an integrated literature review through article searches in the Pubmed, ScienceDirect, Scopus and Google Scholar databases. The results showed that the knowledge and behavior of respondents in preventing tuberculosis increased after being given education using video recordings. In conclusion, there is an effect of health education with video recording on transmission prevention behavior in pulmonary tuberculosis families. Keywords: Family, Prevention, Nurse, Video Recording, Tuberculosis